2015
DOI: 10.1038/sc.2014.197
|View full text |Cite
|
Sign up to set email alerts
|

Spinal intradural abscess caused by hematogenous spread of Prevotella oralis in a 3-year-old child with an asymptomatic congenital spinal abnormality

Abstract: Method: We report a 3-year-old child with progressive paraparesis who was diagnosed with an intradural spinal abscess, epidermoid cyst and dermal sinus. The patient was treated surgically followed by antimicrobial treatment. Result: Intraoperative abscess culture was positive for Prevotella oralis, which has not been reported before as a single isolate in literature. The patient's neurologic status was significantly improved after surgical treatment. Conclusion: Prophylactic antimicrobial therapies should cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…12 We compared our cases with case series and case reports in the literature (►Table 5). 1,8-11, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] In 1917, Elsberg was the first to operate on a spastic paraplegic patient with an SSA. Ten years later, Sittig treated another patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 We compared our cases with case series and case reports in the literature (►Table 5). 1,8-11, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] In 1917, Elsberg was the first to operate on a spastic paraplegic patient with an SSA. Ten years later, Sittig treated another patient.…”
Section: Discussionmentioning
confidence: 99%
“…26,30 30 In patients with minor symptoms, the treatment strategy should be tailored individually. 1,[8][9][10][11][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Based on our experience, laminoplasty is very useful for avoiding posterior instrumentation. 4,6,7 Because we treated our cases urgently, we could not perform intraoperative electrophysiologic monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported etiological causes of SSA are hematogenous dissemination, iatrogenic contamination such as steroid injection, lumbar puncture, or previous spinal surgeries, and local extension [21-25]. In the literature, several studies have reported predisposing factors such as congenital dermal sinus [8, 10, 11, 13, 15], dermoid cysts [13, 15-17], anatomical abnormalities of the spinal cord [18], diabetes mellitus [23], drug abuse, immunodeficiency syndromes, immunosuppressive situations, and repetitive meningitis [8]. In children, intradural extra- and intramedullary infections are more commonly caused by pre-existing congenital abnormalities in the spinal column [3, 8, 10, 11, 22-24].…”
Section: Discussionmentioning
confidence: 99%
“…Spinal intradural abscess is an extremely rare condition, especially in pediatric cases (4). Iatrogenic spinal infections (ISE) are considered possible complications that could arise after spinal surgical procedures (3,9).…”
Section: █ Discussionmentioning
confidence: 99%